2020
DOI: 10.1109/jlt.2020.2981554
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Solar Cells for Outdoor LiFi Communications

Abstract: Increasing demand of wireless devices contributes to radiofrequency (RF) congestion. Light Fidelity (LiFi) promises to be an interesting alternative by using the visible part of the electromagnetic spectrum instead of the RF part as nearly all existing wireless transmission systems do. A basic LiFi system is composed of one intensity-controlled lightemitting diode (LED) and one receiver device sensitive to very high-frequency (thus invisible to human sight) modulations of the luminous intensity. In most cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
0
10
0
1
Order By: Relevance
“…13 , 14 , and more recently, data rates of up to 500 Mb/s from a single gallium arsenide (GaAs) solar cell have been reported by Fakidis et al 7 . This dual function of photovoltaic (PV) systems is beneficially exploited for a wide variety of applications ranging from self-powered long-range free-space optical systems, where a large receiver exhibits significant advantages, to self-powered wearable devices as part of the future IoT 15 . Inorganic PVs, such as silicon (Si) and GaAs, exhibit high power conversion efficiencies (PCEs) (>25%) under solar spectrum illumination (air mass (AM) 1.5 G, corresponding to 100 mW/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 , 14 , and more recently, data rates of up to 500 Mb/s from a single gallium arsenide (GaAs) solar cell have been reported by Fakidis et al 7 . This dual function of photovoltaic (PV) systems is beneficially exploited for a wide variety of applications ranging from self-powered long-range free-space optical systems, where a large receiver exhibits significant advantages, to self-powered wearable devices as part of the future IoT 15 . Inorganic PVs, such as silicon (Si) and GaAs, exhibit high power conversion efficiencies (PCEs) (>25%) under solar spectrum illumination (air mass (AM) 1.5 G, corresponding to 100 mW/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…LiFi can be used both indoor and outdoor. 172 In both cases, but especially outdoor where they outperform photodiode receivers, 173 PV-based receivers could be the solution. Research has shown that conventional PV cell technologies can be used as a receiver in LiFi transmission infrastructures.…”
Section: Research Area 5 Integration and Control Of Light-generatingmentioning
confidence: 99%
“…As water is relatively transparent to blue or green light [2], laser or LED based UWOC technology has attracted much attention as a more promising solution in close range high-capacity underwater communication scenarios [3][4][5][6][7]. However, charging the batteries in UWOC systems in underwater scenarios is usually very expensive and impractical [8], and a promising solution is energy harvesting by UWOC systems, further proposed in [9][10][11][12][13][14][15][16][17] as the SLIPT technique, in which the light signals received by solar cells are used for energy harvesting (EH) and information decoding (ID).…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest experimental reports on SLIPT demonstrated outdoor decoding of VLC signals from an LED source at a rate of 3 kbps using low-cost silicon SC while accomplishing energy harvesting [9]. The authors of [10] compared photovoltaic (PV) modules and avalanche photodiode (APD) detectors for experimental visible light communication (VLC) transmission under outdoor conditions, quantified the attenuation and SNR of both solutions, and demonstrated that PV modules can transmit VLC under outdoor solar illumination. The first experimental demonstration of indoor SLIPT was demonstrated in [11] and data rates of 7 Mbps were reported using a polysilicon solar panel receiver.…”
Section: Introductionmentioning
confidence: 99%